2016
DOI: 10.1371/journal.pone.0151921
|View full text |Cite
|
Sign up to set email alerts
|

Metagenomic Survey of Viral Diversity Obtained from Feces of Subantarctic and South American Fur Seals

Abstract: The Brazilian South coast seasonally hosts numerous marine species, observed particularly during winter months. Some animals, including fur seals, are found dead or debilitated along the shore and may harbor potential pathogens within their microbiota. In the present study, a metagenomic approach was performed to evaluate the viral diversity in feces of fur seals found deceased along the coast of the state of Rio Grande do Sul. The fecal virome of two fur seal species was characterized: the South American fur … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
38
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(39 citation statements)
references
References 65 publications
1
38
0
Order By: Relevance
“…In lung samples of deceased harbor seals along the North American Pacific coast anelloviruses were identified over multiple years demonstrating the persistence of this infection in the population (Ng et al, 2011). Analyses of sub-Antarctic (Arctocephalus tropicalis) and South American fur seal (A. australis) feces also led to the identification of anellovirus sequences (Kluge et al, 2016).…”
Section: Anelloviridaementioning
confidence: 95%
“…In lung samples of deceased harbor seals along the North American Pacific coast anelloviruses were identified over multiple years demonstrating the persistence of this infection in the population (Ng et al, 2011). Analyses of sub-Antarctic (Arctocephalus tropicalis) and South American fur seal (A. australis) feces also led to the identification of anellovirus sequences (Kluge et al, 2016).…”
Section: Anelloviridaementioning
confidence: 95%
“…This far, viral metagenomics studies have covered almost all the major oceans to include the Arctic (Hingamp et al, 2013; Brum et al, 2015; Sunagawa et al, 2015), Antarctic (Suttle, 2005; López-Bueno et al, 2009), sub-Antarctic (Kluge et al, 2016) pacific (Hurwitz and Sullivan, 2013), Indian (Williamson et al, 2012), and Atlantic oceans (Suttle, 2005; Tucker et al, 2011). Based on observations from these studies, the most common environmental factor shown to influence the compositions of viruses in coastal areas used for aquaculture are anthropogenic activities and ecological factors.…”
Section: Factors That Influence the Composition Of Viral Communities mentioning
confidence: 99%
“…This virus has been show to survive up to 15 days in marine water (Smith et al, 1981). Seal poxvirus causes cutaneous lesions resembling other zoonotic parapoxvirus infections such as Orf virus in humans (Hicks and Worthy, 1987; Clark et al, 2005) while rotavirus group C which causes diarrhea in humans was recently isolated from the Antarctica sea fur using viral metagenomics (Kluge et al, 2016). Given that water is a stable medium that allows for the transmission of viruses, the shedding of zoonotic viruses in marine environments could serve as a mode of transmission to humans.…”
Section: Factors That Influence the Composition Of Viral Communities mentioning
confidence: 99%
“…However, the BuV capsid proteins VP1 and VP2 share only 71–78% and 64–73% similarities at the aa level, respectively, generating three genotypes45. Tusavirus on the other hand has been described only in one child2, although partial TuV-like sequences have been detected in fur seals in Brazil6.…”
mentioning
confidence: 99%
“…BuV-like viruses have been found in wild and captive non-human primates as well as in swine, shrews, rats, bats and fur seals46121314151617. The detection of these viruses in sera of rhesus monkeys in the USA, and in the spleen of wild baboons and shrews in Zambia, suggests that BuV-like viruses may cause systemic infections1213.…”
mentioning
confidence: 99%